Associations of C-RP with Renal Function Group and some Clinical Parameters in Patients with Dialysis in Iraq - Eatmad Abed Ali Alshawi; Ziena Mohammad Hatem; Athraa Adnan Mahdi (International Journal of Biochemistry and Biomolecule Research, 2026)
Introduction: Chronic kidney disease is a disease for which there are high mortality rates among those infected with many complications, including high rates of inflammation, anaemia, osteoporosis, and other complications. Methods: The current study was designed to evaluate the kidney functions of patients undergoing dialysis, where levels were evaluated Urea, Uric Acid, and Creatinine, in addition to C-Reactive Protein as a progressive of inflammation parameter, and to evaluate anaemia levels in patients. This study will be conducted in the Department of Medical Laboratory Techniques, Al-Furat Al-Awsat Technical University, and the Specialized Centre for Kidney Diseases and Transplantation, Sadr Medical City, Najaf Governorate. Results: A total of 39 patients with chronic renal failure undergoing maintenance haemodialysis who were admitted to the hospital from March 2022 to January 2022 were selected as subjects. All parameters CRPmg/LS.cr μmol/L, S. urea(mmol/L), S.Uric acid(mg/dl), Albumin(g/dl), Haemoglobin(g/L), iron μmol/L, RBCs, WBCs p-value ˂0.05 between case-control study are Statistically significant. Conclusion: High inflammatory rates and increased anaemia are among the most important signs accompanying chronic kidney failure and those undergoing dialysis. High inflammatory rates and high urea and creatinine are among the causes of future complications in patients, which are the main cause of death.
Keywords: C-reactive protein; CRF; Creatinine iron; Urea; Uric acid; dialysis